SUSTAINABLE MARKETING STRATEGY THROUGH SOCIAL MEDIA AS A SUPPORTING FORCE FOR FOOD SECURITY IN CHILI AND TOMATO SEED PRODUCTS - Sefi Lefberti Arisanto; Hadiah Fitriyah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the marketing strategies of chili and tomato seedlings through social media and analyzes the role of delivery services in enhancing marketing success and contributing to local food security. Method: A descriptive qualitative approach was applied, utilizing in-depth interviews, observations, and documentation with seedling farmers in Bojonegoro Regency. Results: The research reveals that Facebook and WhatsApp are the most effective platforms for promoting seedlings due to their accessibility and strong community engagement. Marketing strategies such as visual content sharing, customer testimonials, and educational posts were found to significantly increase consumer trust and market reach. The study also emphasizes that efficient, secure, and affordable delivery services are crucial for maintaining the quality and viability of horticultural seedlings during distribution. Novelty: This research underscores the synergistic relationship between digital marketing and logistics as a sustainable model for strengthening farmers’ economic resilience and ensuring the availability of high-quality seedlings, thereby reinforcing regional food security.